Characterizing sequence variation in the VP1 capsid proteins of foot and mouth disease virus (serotype 0) with respect to virion structure. - Haydon, D; Lea, S; Fry, L; Knowles, N; Samuel, A; Stuart, D; Woolhouse, M (1998)
The VP1 capsid protein of foot and mouth disease virus (FMDV) is highly polymorphic and contains several of the major immunogenic sites important to effective antibody neutralization and subsequent viral clearance by the immune system. Whether this high level of polymorphism is of adaptive value to the virus remains unknown. In this study we examined sequence data from a set of 55 isolates in order to establish the nature of selective pressures acting on this gene. Using the known molecular structure of VP1, the rates and ratios of different types of nonsynonymous and synonymous changes were compared between different parts of the protein. All parts of the protein are subject to purifying selection, but this is greatest amongst those amino acid residues within beta-strands and is significantly reduced at residues exposed on the capsid surface, which include those residues demonstrated by previous mutational analyses to permit the virus to escape from monoclonal antibody binding. The ratios of nonsynonymous substitution resulting in various forms of physicochemically radical and conserved amino acid change were shown to be largely equal throughout these different parts of the protein. There was a consistently higher level of nonsynonymous and charge radical sites in those regions of the gene coding for residues exposed on the outer surface of the capsid and a marked difference in the use of amino acids between surface and nonsurface regions of the protein. However, the analysis is consistent with the hypothesis that the observed sequence variation arises where it is least likely to be disruptive to the higher-order structure of the protein and is not necessarily due to positive Darwinian selection.